Networking for digital preservation : current practice in 15 national libraries. - Verheul, Ingeborg (2006)
Report presenting the outcome of a study on recent developments in digital preservation in fifteen national libraries.
Keywords: CONSERVACION DE DOCUMENTOS; DIGITALIZACIÓN DE LA INFORMACIÓN; BIBLIOTECAS NACIONALES; REDES DE INFORMACIÓN; INFORMACION ELECTRONICA